1996
DOI: 10.1111/j.1365-2133.1996.tb03610.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and appropriateness of general practitioner referrals to a dermatology out-patient clinic

Abstract: A study was undertaken of new referrals by GPs to a dermatology clinic in a district general hospital over a 6-month period. Six hundred and eighty-six consecutive referrals to one consultant were analysed for diagnostic accuracy and requirement for referral. Only 47% of referral letters contained the correct diagnosis. Viral warts and psoriasis were best diagnosed (82 and 78%, respectively), but seborrhoeic warts and dermatofibromas caused difficulty (22 and 19%, respectively). Cutaneous malignancy was correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
3
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 13 publications
2
32
3
5
Order By: Relevance
“…Interestingly, our results are similar to studies of referral quality in other medical specialties, which have shown that 48% of mental health referrals (18), 43% of referrals for dementia (19) and 21% of dermatology referrals (20) were for conditions that could have been managed without the need of a specialist. Educational and organizational strategies to decrease these referrals have been shown to have a significant effect on reducing wait times (21) and, therefore, could also be of use in the musculoskeletal domain.…”
Section: Figure 1) Flowchart Illustrating the Breakdown Of New Outpatsupporting
confidence: 79%
“…Interestingly, our results are similar to studies of referral quality in other medical specialties, which have shown that 48% of mental health referrals (18), 43% of referrals for dementia (19) and 21% of dermatology referrals (20) were for conditions that could have been managed without the need of a specialist. Educational and organizational strategies to decrease these referrals have been shown to have a significant effect on reducing wait times (21) and, therefore, could also be of use in the musculoskeletal domain.…”
Section: Figure 1) Flowchart Illustrating the Breakdown Of New Outpatsupporting
confidence: 79%
“…Though it has been suggested that the ability of a primary care physician to diagnose skin complaints could be poor compared with a dermatologist, 27 psoriasis is one of the skin disorders best diagnosed by the GP according to results from a study in the United Kingdom. 27 In line with the study conducted in Rochester, Minnesota, 9 we found the incidence to slightly increase gradually with age up to the seventh decade of life in men and women. Our data also show, as suggested in some case series of psoriasis, a bimodal curve in the age distribution of the incidence of psoriasis.…”
Section: Commentmentioning
confidence: 99%
“…We considered a patient as a case of psoriasis even when a specialist did not make the diagnosis because, based on the existing literature, most cases in the United Kingdom are not referred for diagnosis to a specialist. 26,27 Finally, after manual revision of the computer medical profiles, 4110 patients were considered as possible cases of psoriasis. We conducted a validation study to evaluate the accuracy of our psoriasis assessment and requested the confirmation of the diagnosis by the GPs in a random sample of 564 patients (approximately 14%).…”
Section: Psoriasis Cases Ascertainment and Validationmentioning
confidence: 99%
“…34 Recent studies have focused on using trained specialist nurses or physiotherapists to triage patients or to undertake specific treatment roles, or on reducing the use of an outpatient visit as a gateway to investigations such as endoscopy. 35,36 Reducing the numbers of patients followed up in clinics creates slots for new patients.…”
Section: Box 1 Principles For Running Outpatient Clinics Suggested Bmentioning
confidence: 99%